Modelling Northern Ireland within the context of the all-island economy - Adele Bergin; Hailey Low; Stephen Millard; Akhilesh Kumar Verma (The Economic and Social Research Institute (ESRI), 2025)
Northern Ireland occupies a unique position following Brexit and the Windsor Framework. It is part of the UK fiscal, welfare and monetary unions - where the main policy levers are mostly exercised at a UK national level - along with its national economic policies for devolved administrations and regions. Simultaneously, it remains within the EU Single Market for goods with Dual EU/UK regulatory regimes, participates in the Common Travel Area (CTA) between the United Kingdom and Ireland and is supported by a commitment to continue specified areas of North-South cooperation. The economic effects of this will continue to evolve over time. Whatever the background situation, it is clear that the economies of both Northern Ireland and Ireland can have a mutually beneficial impact on each other through improved economic outcomes on both sides of the border and enhanced interaction. This report discusses the development of a model for the Northern Ireland economy. The model can be used to produce economic forecasts and to examine the effects of economic policies and shocks. The framework captures the various linkages between the Northern Ireland economy and that of Ireland and so aids our wider understanding of how the Northern Ireland economy functions within the context of the wider all-island economy. The modelling framework also captures linkages to Great Britain and the international economy. By developing such a model and ensuring that the unique features of the Northern Ireland economy - that it is part of the United Kingdom while also being part of the EU Single Market - are built into the model, we can better understand the evolution of the Northern Ireland economy and what it means for the all-island economy. (...)
Keywords: 330